Clinical Eﬃcacy of Ceftazidime-Avibactam in the Treatment of Infections Caused by Carbapenem–Resistant Gram-Negative Bacteria - S. V. Yakovlev (Антибиотики и Химиотерапия)
The wide spread of carbapenemases among gram-negative bacteria of the Enterobacterales order in hospitals around the world, including Russia, creates great difficulties in the effective use of antibiotics for these infections in the ICU. Ceftazidime-avibactam is the first antibiotic developed and studied for the treatment of infections caused by carbapenem-resistant enterobacteria. Ceftazidime-avibactam shows high activity against producers of class A and D serine carbapenemases (KPC and OXA-48). In combination with aztreonam it is effective in infections caused by producers of class B metallo-beta-lactamases (NDM and VIM). The review analyzes the results of 19 non-comparative and 10 comparative studies of ceftazidime-avibactam in infections caused by carbapenem-resistant Enterobacterales, as well as case reports. According to the data of non- comparative studies, the clinical efficacy of ceftazidime-avibactam ranged from 45.0 to 87.2%, on average 71.7±11.3%, and the eradication rate of KPC or OXA-48 carbapenemase producers ranged from 40.0 to 100%, on average 65.5±18.6%. The effectiveness of ceftazidime-avibactam in comparative studies was 67.9±17.3%, which was significantly higher compared to other antibiotics (44.3±14.4%, P=0.012). Treatment with ceftazidime-avibactam was accompanied by a significantly lower 30-day mortality in contrast to other antibiotics – 23.8±13.5% and 41.0±13.6%, respectively, P=0.001. The development of resistance in Enterobacterales species to ceftazidime-avibactam during therapy is rarely observed, on average 5.4±4.4%, which characterizes a rather low potential of the antibiotic in resistance selection. Early administration of ceftazidime-avibactam is accompanied by better treatment results as opposed to delayed therapy. Treatment of infections caused by carbapenem-resistant enterobacteria with ceftazidime-avibactam is associated with a significantly higher recovery rate and a lower mortality compared to other regimens of antibacterial therapy.